Typological features of visual generated potential by children with neurosensory bradyacuasia - G. Sh. Gafijatullina; E. V. Trofimova (Кубанский научный медицинский вестник, 2015)
Character of the central nervous system functions damage influences a feature of generation visual generated potential (VGAP) components by children with neurosensory bradyacuasia (NSB). The configurations of early and late reductants of the VGAP differ for hard of hearing and healthy children. At NSB the amplitude of negative reductant is reduced in frontal, temporal and occipital regions of both brain hemispheres as contrasted to by control. The decrease of amplitude of VGAP positive reductants are connected to failure the hard of hearing children attention function.